(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
To investigate the effective dose combination of modafinil and caffeine by estimating nootropic activity for the management of narcolepsy. The effective dose combination of modafinil and caffeine was determined by the evaluation of nootropic activity in male albino rats of the wistar strain. Modafinil and caffeine were administered in combination to test group 1, II and III orally, followed by scopolamine to induce amnesia. The dose of modafinil was kept constant at 50 mg/day, while the dose of caffeine was reduced gradually in all the treatment groups. Modafinil alone at a dose of 200 mg/day was used as a standard drug. Different parameters like body weight, transfer latency, and escape latency were considered for the evaluation of nootropic activity. The combinational index was determined by the method of Chou-Talalay. The result indicates that the reduction in escape and transfer latency (p<0.001 respectively) of group VI (modafinil at a dose of 50 mg/day with caffeine at a dose of 30 mg/day) was evident as compared to the negative control group on day 28. The evaluation of the effective dose combination of modafinil and caffeine for the management of narcolepsy against scopolamine-induced amnesia demonstrated significant improvements in cognitive performance, as indicated by reduced escape and transfer latency levels.